Semi-selective medium for Fusarium graminearum detection in seed samples - Segalin,Marivane (2010)
Fungi of the genus Fusarium cause a variety of difficult to control diseases in different crops, including winter cereals and maize. Among the species of this genus Fusarium graminearum deserves attention. The aim of this work was to develop a semi-selective medium to study this fungus. In several experiments, substrates for fungal growth were tested, including fungicides and antibiotics such as iprodiona, nystatin and triadimenol, and the antibacterial agents streptomycin and neomycin sulfate. Five seed samples of wheat, barley, oat, black beans and soybeans for F. graminearum detection by using the media Nash and Snyder agar (NSA), Segalin & Reis agar (SRA) and one-quarter dextrose agar (1/4PDA; potato 50g; dextrose 5g and agar 20g), either unsupplemented or supplemented with various concentrations of the antimicrobial agents cited above. The selected components and concentrations (g.L-1) of the proposed medium, Segalin & Reis agar (SRA-FG), were: iprodiona 0.05; nystatin 0,025; triadimenol 0.015; neomycin sulfate 0.05; and streptomycin sulfate, 0.3 added of ¼ potato sucrose agar. In the isolation from seeds of cited plant species, the sensitivity of this medium was similar to that of NSA but with de advantage of maintaining the colony morphological aspects similar to those observed in potato-dextrose-agar medium.